Rancang Bangun Turbine Micro Hydro - Yose Rizal; Suryana Bayu Wijaya; Syahid Tri Kusuma Wijaya AL Muhyi; Muhamad Taufik (Jurnal Inovasi Mesin, 2023)
Design of a Mini Hydro Turbine-based Hydro Power Plant as an effort to maximize Renewable Energy in Indonesia.